Adjuvant chemotherapy in colon cancer: state of the art and future perspectives. Issue 4 (July 2020) - Iveson, Tim
Abstract : Purpose of review: This article will review the results of recent studies, which have investigated the duration of adjuvant chemotherapy and also suggest, which aspects of adjuvant treatment need investigation in future studies. Recent findings: The IDEA collaboration investigated whether the duration of adjuvant chemotherapy with an oxaliplatin doublet could be reduced from 6 to 3 months. Although this study did not demonstrate noninferiority for 3 months treatment, it did show noninferiority for patients receiving 3 months CAPOX chemotherapy and for those patients with low-risk stage III disease receiving 3 months' treatment. There was also significantly less toxicity seen with 3 months' treatment. Recent studies have shown that detectable ctDNA postoperatively can predict those patients most likely to relapse and so benefit from adjuvant treatment. Summary: It has been shown that for patients receiving adjuvant CAPOX chemotherapy, or those receiving adjuvant chemotherapy for low-risk stage III colon 3 months' chemotherapy gives similar outcomes to 6 months' treatment with significantly less toxicity.